Odpowiedzi

Najlepsza Odpowiedź!
2009-11-06T22:01:28+01:00
Cos(2x+PI/3)=1/2
musisz wiedziec, że cosα=1/2 gdy α=π/3 +2kπ, α= -π/3 +2kπ

czyli:
2x+PI/3=π/3 +2kπ lub 2x+PI/3= -π/3 +2kπ
2x=π/3 +2kπ-π/3 lub 2x= -π/3 +2kπ-π/3
2x=2kπ lub 2x= -2π/3+2kπ
x=kπ lub x= -π/3+kπ , k∈C
1 1 1
2009-11-06T22:31:54+01:00

cos (2x +pi/3) = 1/2

2x + pi/3 = pi/3 + 2pi*k        lub    2x + pi/3 = - pi/3 + 2pi*k

2x = 2pi*k           lub    2x = - (2/3) pi + 2pi*k

x = pi*k                lub      x = - pi/3 + pi*k , gdzie k  - dowolna liczba całkowita

===========================================================

2 3 2